Detection of nosocomial Clostridium difficile infections with toxigenic strains despite negative toxin A and B testing on stool samples. (20th February 2014) - Stahlmann, J.; Schönberg, M.; Herrmann, M.; von Müller, L.; Allerberger, F.
Abstract A two‐step diagnostic algorithm is recommended to detect Clostridium difficile infections; however, samples are regularly found that are glutamate dehydrogenase (GDH) positive but stool toxin negative. In the present single‐centre prospective study we focused on these 'difficult‐to‐interpret' samples and characterized them by anaerobic culture, toxigenic culture, slpA sequence typing and multiplex PCR (GenoType CDiff). The majority of stool toxin A and B‐negative samples have been caused by toxigenic strains including ribotype 027. The multiplex PCR was faster and more sensitive compared with culture and allowed preliminary identification of hypervirulent strains in stool samples on the same day.